Virucidal activity of the antiseptic mouthwash and dental gel containing anionic phthalocyanine derivative: In vitro study - Santos, Caique; Orcina, Bernardo da Fonseca; Reia, Verônica Caroline Brito; Ribeiro, Lucas Gabriel [UNESP]; Grotto, Rejane M. T. [UNESP]; Prudenciatti, Aruã [UNESP]; de Moraes, Leonardo Nazario [UNESP]; Zangrando, Mariana Ragghianti; Vilhena, Fabiano Vieira; Santos, Paulo Sérgio da Silva (Taylor & Francis, 2021)
Aim: This research suggested an in vitro virucidal action of a dental gel and a mouthwash with phthalocyanine derivative. Purpose: The aim of this study was to report an in vitro study evaluating the virucidal capacity of mouthwash and dental gel containing anionic phthalocyanine derivate (APD). Methods: The research followed the recommendations of the National Health Surveillance Agency (ANVISA) and adapted methodology, described in the standards EN14776: 2015; ASTM E1053-11 and the Robert Koch Institute – RKI, in addition to good laboratory practices (GLP). The determination of the percentage of inactivation of the SARS-CoV-2 virus particles was carried out by imposing the viral solution in contact with the respective tested products, with intervals of 30 seconds, 1 and 5 minutes, with subsequent submission of the aliquots, recovered in cell culture microplates following virus titration using the TCID50 (50% Median Tissue Culture Infectious Dose). Results: The Mouthwash APD presented 90% of viral inactivation percentage, while the dental gel APD demonstrated 99.99% of viral inactivation. Conclusion: In vitro analyses showed that mouthwash and dental gel APD can reduce the viability of SARS-CoV-2 virus particles.
Keywords: Coronavirus infections; Dentifrices; In vitro techniques; Mouthwash